Cardiovascular Risk Factors in a Suburban Community in Nigeria - Titilope Modupe Dokunmu; Omolara Faith Yakubu; Abiodun Humphrey Adebayo; Grace Iyabo Olasehinde; Shalom Nwodo Chinedu (International Journal of Hypertension)
The burden of hypertension, a silent killer, continues to increase in low- and middle-income countries. This study evaluated blood pressure (BP) in healthy adults to determine their risk of developing hypertension and to reduce associated morbidity of the disease. Overall, 182 subjects aged >16 years participated in the study. Systolic (SBP) and diastolic blood pressure (DBP) was measured after a resting period using mercury sphygmomanometer. Random blood glucose (RBG) concentration was also determined. Regression models were used to determine risk of high BP with p values < 0.05 indicating statistical difference. Prehypertension was present in 36.8% population and high BP in 31% individuals with hypertensive symptoms. DBP ≥ 90 mmHg was prevalent in the undiagnosed group, while diabetes comorbidity was detected in only 4 individuals. High BP or diabetes was not detected in those <20 year olds. Age > 35 years was an independent risk (likelihood ratio: 22.56, p<0.0001); this increases to 26.48 (p<0.0001) in the presence prediabetes and RBG > 100 mg/dl. Undiagnosed hypertension rate is high in the study area, and urgent interventions for large scale screening and management of the disease are required to reduce the burden of hypertension in Nigeria.